Reflexões sobre um curso de ecologia por correspondência: indícios do processo formativo a partir de documentos arquivados - Silva, Maria Fernanda Rosa da (Universidade Federal de São Carlos, 2023)
Zoos are very important institutions that perform social and environmental functions, one of their pillars being environmental education. The municipal zoo Quinzinho de Barros, in Sorocaba, was considered the precursor in environmental education activities in the 1970s and 1980s, and one of the activities carried out during this period was the production of a series of comics for children entitled: “Ecology course by Correspondence". This work aimed to discuss the content contained in the covers of the second edition of the course, performing a preliminary analysis of the knowledge that was passed on during that time. Based on the analysis, it is indicated that the objective of the course was not to teach content related to the area of science entitled ecology, but rather to use this vehicle as a way of disseminating environmental education. It is also possible to infer that the course focuses on a more “naturalist” and “conservative” tendency towards environmental education, which was very common at the time.Based on the analysis, it is indicated that the objective of the course was to teach subjects related to ecology, but mainly to use this vehicle as a way of disseminating environmental education. It is also possible to infer that the course focuses on a more “naturalistic” and “conservative” trend of environmental education, which was very common at the time.
Reflections on a correspondence ecology course: signs of the formative process based on archived documents
Keywords: Ensino de Ecologia; Educação Ambiental; Zoológicos; Ecology Teaching; Environmental Education; Zoos; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO